(untitled) (Research, Society and Development, 2022)
This article deals with a study on the consequences of Neoliberalism aimed at public education policies in Brazil. Thus, the general objective of this research is to analyze how Neoliberalism was able to influence the insertion of educational public policies in that State. As a research methodology, a bibliographic study was used based on the theoretical knowledge of Merquior, Locke, Bobbio, Harvey, Konder, Freitas, Miranda, among others. From this perspective, the research result demonstrated, based on the classics, and in a brief reflection, that the historicity in which Neoliberalism was forged represents an instigating scenario, and that through political articulations a new history for educational public policies was being unveiled in the eyes of the citizen, which led, therefore, to reflect on aspects of contemporary education from the perspective of the Brazilian State. Finally, it was found that this study enabled a discussion and visualization of developments on contemporary reality, paying attention to the changes in social policy in education, attributed to the policy of the neoliberal State.